Ilmenite as low-cost catalyst for producer gas quality improvement from a biomass pilot-scale gasifier. (February 2020) - Pio, D.T.; Gomes, H.G.M.F.; Tarelho, L.A.C.; Ruivo, L.C.M.; Matos, M.A.A.; Pinto, R.G.; Frade, J.R.; Lemos, F.M.S.
Abstract: In this work, in-situ application of natural occurring ilmenite (FeTiO3 ) for upgrading the producer gas from a pilot-scale bubbling fluidized bed gasifier was performed and its influence on the gas characteristics and gasifier performance was analyzed. Without using ilmenite, the producer gas average composition (volumetric basis, dry gas) was 15.2% CO, 7.6% H 2, 3.8% CH4 and 15.6% CO2, with 0.50 H 2 :CO molar ratio and 5.0 MJ/Nm 3 lower heating value. For this condition, 1.6 Nm 3 gas/kg biomass (dry basis) specific dry gas production, 44.5% cold gas efficiency and 68.4% carbon conversion efficiency were attained. Using ilmenite as catalyst, the producer gas average composition (volumetric basis, dry gas) was 13.9% CO, 11.7% H 2, 4.0% CH4 and 17.9% CO2, with 0.84 H 2 :CO molar ratio and 5.1 MJ/Nm 3 lower heating value. For this condition, 1.7 Nm 3 gas/kg biomass (dry basis) specific dry gas production, 49.8% cold gas efficiency and 75.5% carbon conversion efficiency were attained. Thus, in-situ application of ilmenite generally improved the gasifier performance and induced an increase of H 2 concentration and H 2 :CO molar ratio in the producer gas of 35.1% and 40.7%, respectively, improving its suitability for advanced gas applications that require high H 2 :CO ratios, such as liquid fuels and chemicals synthesis.